Young carers in Australia:understanding the advantages and disadvantages of their care giving - Hill, T; Cass, B; Hamilton, M; Smyth, C; Blaxland, M (My University, 2009)
'Young carers’ is the term used in Australia and the UK to refer to children and young adults with informal caring responsibilities for other people—usually, but not always co-resident family members who have a chronic illness, physical or mental disability or are frail aged. This paper examines the impact of caring on young carers and identifies a number of issues relevant to policy development.
Social Policy Research Paper
Keywords: Carers; Families and relationships; Carers; Families and relationships